1991
DOI: 10.1111/j.1432-1033.1991.tb16147.x
|View full text |Cite
|
Sign up to set email alerts
|

Kluyveromyces lactis toxin has an essential chitinase activity

Abstract: The Kluyveromyces lactis toxin is a protein containing three subunits (alpha, beta and gamma) which causes sensitive yeast cells to arrest proliferation in the G1 phase of the cell cycle. Despite the toxin's complex structure, the gamma subunit appears to be the only component required for it to arrest proliferation since intracellular expression of the gamma polypeptide alone in a sensitive yeast strain mimics the effect of the exogenous native toxin. The toxin alpha subunit shows sequence similarity to a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 20 publications
3
64
0
Order By: Relevance
“…Consistent with an impact on early events, class I mutations in KTI2/CHS3 and KTI10/ PMA1 protect solely against exozymocin and affect chitin synthesis and plasma membrane H ϩ -ATPase function, respectively (11,33,43). In line with this, holozymocin binds chitin in vitro and has exochitinase activity (10,33). As judged from the finding that hygromycin B, whose antibiotic action requires an intact membrane potential established by H ϩ -ATPase Pma1/ Kti10, is inert against kti10 cells, plasma membrane energization is likely to be required for zymocin action (43,50).…”
supporting
confidence: 50%
“…Consistent with an impact on early events, class I mutations in KTI2/CHS3 and KTI10/ PMA1 protect solely against exozymocin and affect chitin synthesis and plasma membrane H ϩ -ATPase function, respectively (11,33,43). In line with this, holozymocin binds chitin in vitro and has exochitinase activity (10,33). As judged from the finding that hygromycin B, whose antibiotic action requires an intact membrane potential established by H ϩ -ATPase Pma1/ Kti10, is inert against kti10 cells, plasma membrane energization is likely to be required for zymocin action (43,50).…”
supporting
confidence: 50%
“…However, the cx and 3 subunits are required for the native toxin to act from the cell exterior (54). The cx polypeptide shows sequence similarity to plant and bacterial chitinases (4,49) and exhibits a chitinase activity against model chitin substrates (6). Together with the finding that chitin-deficient mutants are toxin resistant (33,53), this observation suggests a role for the ox polypeptide in the binding of the toxin to cell wall chitin.…”
mentioning
confidence: 52%
“…Such mutations might conceivably affect a cell surface toxin receptor or affect cell surface components required for toxin internalization. We have previously shown that the toxin exhibits a chitinase activity against a specific model chitin substrate (6). This activity is essential for the activity of the protein as a yeast toxin, and we have therefore postulated that the initial interaction of the toxin with sensitive cells may be via binding to chitin in the cell wall.…”
Section: Methodsmentioning
confidence: 99%
“…cerevisiae (Cabib et al, 1992) and yeast Kluyveromyces lactis toxin (Butler et al, 1991). It has poorer activity against bacterial chitinases Somers et al, 1987;Koga et al, 1987) and no detectable activity against the plant chitinase from yam (Koga et al, 1987).…”
Section: Discussionmentioning
confidence: 99%